CONNOTATIVE MEANING IN MICHAEL JACKSON’S SONG LYRIC “HEAL THE WORLD”: A SEMANTIC STUDY - Iis Sujarwati; Sari, Nova Pandan (Corolla International Conference, 2022)
This research was concerned on semantic study. It was aimed to describe the connotative words meaning used by the songwriter and to explain the message delivered in Michael Jackson’s song lyrics. This research employed a descriptive qualitative method involving one song lyrics by Michael Jackson entitled “Heal the World”. The data were collected by downloading and listening to the song, reading the lyrics, and analyzing the connotative words. The findings viewed that there were totally eleven connotative meanings founded in “heal the world” song lyrics in 3 types, such as 8 positive connotations, 2 negative connotations, and 1 neutral connotation. Furthermore, the researchers also identified 3 main messages in this song lyric. The first is heart as a symbol of someone’s sincerity. The second is become a good person is not difficult. The last is nothing impossible to make this world much better as long as we have the intention. From these messages, the researchers concluded that the main message of this song is invited the listeners to fix our world in order to have a sense of love and peach even though our body is dying. Therefore, the world will be better if we are sharing love each other.